Multiple primary and secondary sources for chemically similar obsidians from the area of portada covunco, west-central Neuquén, Argentina - Stern, C. R. (2012)
In west-central Neuquén Province, Argentina, in the area around Estancia Llamuco, west of Zapala, south of Las Lajas and north-east of Lago Aluminé, there are multiple primary and secondary sources of obsidian. Primary sources occur within the south-east extension of the Plio-Quaternary volcanic chain that runs from Copahue volcano through Pino Hachado. Secondary sources include river-bed gravels within the valleys of Arroyo Cochicó Grande and Río Kilca as far south as where this river joins with Río Aluminé, and the Quaternary fluvial-glacial sediments cut by the valley of Río Covunco as far east as Portada Covunco. Visually variable obsidians from these two secondary sources include homogeneous black and grey-translucent types, porphyritic and banded types, and an abundant quantity of oxidized red and black obsidian. However, all these visually distinct obsidians have similar and unique chemistry, with Ba between 220 and 340ppm, different from any other obsidians previously reported from Neuquén, which all have Ba>500ppm, as do obsidians from sources to the north in Mendoza and to the west in Chile. This chemical distinctive obsidian has been exploited and transported over a wide area, beginning prior to 4000 bp, and occurs in local archaeological sites, as well as sites ≥ 300km to the north-east in La Pampa Province, ~430km to the south in Chubut Province, and >75km to the west across the Andean drainage divide in Chile.